High-intensity Interval Training: A Review of Its Impact on Glucose Control and Cardiometabolic Health - Cassidy, S; Thoma, C; Houghton, D; Trenell, MI (Springer Nature, 2017)
Exercise plays a central role in the management and treatment of common metabolic diseases, but modern society presents many barriers to exercise. Over the past decade there has been considerable interest surrounding high-intensity interval training (HIIT), with advocates claiming it can induce health benefits of similar, if not superior magnitude to moderate-intensity continuous exercise, despite reduced time commitment. As the safety of HIIT becomes clearer, focus has shifted away from using HIIT in healthy individuals towards using this form of training in clinical populations. The continued growth of metabolic disease and reduced physical activity presents a global health challenge and effective therapies are urgently required. The aim of this review is to explore whether the acclaim surrounding HIIT is justified by examining the effect of HIIT on glucose control, its ability to affect cardiovascular function and the underlying mechanisms of the changes observed in those with common metabolic diseases. It also explores translation of the research into clinical practice.
Keywords: Cardiovascular system; Exercise; Exercise therapy; Metabolic diseases; Metabolism; Physical fitness; Review; Weight loss